Given the following functions f(x) and g(x), solve (f ⋅ g)(3) and select the correct answer below:

f(x) = 4x2 + 12

g(x) = x − 1

47
−47
96
−96

Respuesta :

The first thing we must do for this case is multiply both functions:
 f (x) = 4x2 + 12
 g (x) = x - 1
 Multiplying we have:
 (f ⋅ g) (x) = (4x2 + 12) * (x - 1)
 We rewrite:
 (f ⋅ g) (x) = 4x3 - 4x2 + 12x - 12
 We evaluate for x = 3:
 (f ⋅ g) (3) = 4 (3) 3 - 4 (3) 2 + 12 (3) - 12
 (f ⋅ g) (3) = 96
 Answer:
 
(f ⋅ g) (3) = 96

Answer:

(f ⋅ g) (3) = 96

ACCESS MORE